Higher BTX yield in coaromatization of n-hexane and methanol over [Zn, Ga]/HZSM-5 catalyst. (15th April 2023) - Li, Haibo; Zhu, Bing; Wang, Xue; Lv, Junmin; Fan, Subing; Zhao, Tiansheng
Graphical abstract: Highlights: The coaromatization of n -hexane and methanol over [Zn, Ga]/HZ was investigated. The modification greatly tunes the acid distribution and increases the L/B ratio. The further introduction of Ga significantly increases the active center Zn(OH) + . The organic species detected in [Zn, Ga]/HZ channels showed more aromatics precursors. The aromatics yield was enhanced greatly from 30% of HZ to 70%. Abstract: A series of [Zn, Ga]/HZ catalysts were prepared by impregnation and their catalytic performance in coaromatization of n -hexane and methanol, a heat-coupling reaction, were studied in detail. The crystallization, textural properties, morphology, acidity, composition and chemical state were characterized by XRD, N2 adsorption/desorption isotherms, TEM, py-FTIR, ICP-OES and XPS. The modification of Zn and Ga tunes the acid distribution, and more importantly Ga introduction greatly increases the content of active centers Zn(OH) + from 30 % (1Zn/HZ) to 60 %. As a result, [Zn, Ga]/HZ improves the dehydroaromatization ability and provides higher aromatics yield. The analysis of organic species in catalyst by TG and GC–MS confirms that [Zn, Ga]/HZ produces more aromatics precursors than HZ. Under the conditions of feed ratio ( n -hexane/methanol) 3:7, reaction temperature 530 °C, and WHSV 1.0 h −1, the BTX yield was significantly increased to 70 %.